Exploitative sham marriages as a form of human trafficking in the European Union - Tikka, Riina Maria (2022)
The aim of this research is to analyse exploitative sham marriages as a form of human trafficking. While there exist several studies focusing on other forms of human trafficking and their impact on societies, little research has been conducted on sham marriages as a form of trafficking in human beings. This dissertation pursues to deepen the knowledge in this area within the scientific field of Criminology, exploring how exploitative sham marriages are prevented in the European Union. Using documentary analysis as a research method, this dissertation examines how academics, international institutions and agencies understand and define sham marriage in different publications, and how sham marriages and exploitative sham marriages are regulated in the criminal codes of the EU countries. Since gathering comparable information from all 27 EU countries was not possible due to limitations of time, language and amount of public data, the action measures executed in the Baltic states are utilized as a case study to represent how victim identification and training of experts are proceeding in the field of human trafficking and sham marriages. Nevertheless, whenever possible, data on other EU countries are used to enhance the comprehensiveness of the analysis. The findings of this research show that the current national and international policies in the EU do not support an effective counterstrategy against exploitative sham marriages, resulting in inadequate victim identification, lack of tools to convict traffickers and therefore inaccurate statistics of the crime. Based on those findings, several recommendations are provided, in particular, about the need of a clear and encompassing definition for sham marriage and exploitative sham marriage, the importance of harmonizing criminal legislation among EU countries, of raising awareness (including general population and vulnerable groups), as well as of encouraging systematic cooperation between EU countries and the actors working in the field of human trafficking.